EXPLORING NATIONALISTIC INSIGHT VALUE IN ADMINISTRATOR LEADERSHIP TRAINING USING UPIN-IPIN MOVIE IN INDONESIA - Suharsono, Agus (Sanata Dharma University Yogyakarta, 2022)
Indonesian government has launched National Culture and Character Education” in 2010 as a national movement to grow nationalistic insight. Nationalistic insight is one of materials in Administrator or 3rd Echelon Official Leadership Training. Widyaiswara (trainers) should develop learning method in order to be more attractive and impressive, and to achieve the objective of learning. Learning using movie (film) media can evidently affect the achievement of learning objective positively and significantly. This research will study and explore nationalistic insight values using Upin-Ipin movie. The method employed was post-test quasi-experiment one. Data was collected using questionnaire (google form), to be analyzed then using logico-inductive method, and presented descriptively. The result of research shows that the learning method, according to participants, has dominant weakness as it has Malaysian background rather than Indonesian. But it also has strength as it facilitates the participants to understand the material of nationalistic insight values. The nationalistic insight value contained in Upin-Ipin movie is social diversity supported with tolerance, mutual respect, and love for motherland. For this method to be better, the participants recommend the trainers to determine the episode of movie that will be used as learning material, to be watched and discussed jointly.